KOREOGRAFI TARI ZAPIN KAMPONG BOLAK DI KECAMATAN TEMBILAHAN KABUPATEN INDRAGIRI HILIR PROVINSI RIAU - Nadila, Sagita Dwi; Mansyur, Herlinda (SENDRATASIK UNP, 2019)
Abstract The purpose of this study is to reveal and describe the ZapinKampong Bolak dance in Tembilahan District, Indragiri Hilir Regency, Riau Province based on Choreography aspect. This type of studywas a qualitative with using descriptive methods. The main instrument in this study was the researcher and was assisted by supporting instruments such as stationery and camera. The type of data used primary and secondary data. Techniques of Data collection were carried out by taking literature study, observation, interviews and documentation. The steps in analyzing data were done by collecting, reducting, presentating and drawing data conclusions. The result shows that the Zapin Kampong Bolak Dance in Citra Sebati Studio Tembilahan District, Indragiri Hilir Regency, Riau Province is a dance that illustrates the life and excitement of young people who do not become arrogant when meeting their friends in the village even though each of them has been successful overseas. The Zapin Kampong Bolak dance is played by a group of dancers  that are consisting of eight dancers and is divided into two male dancers and six female dancers. TheZapin Kampong Bolak dance has dance elements such as motion, music, themes, costumes, make-up, floor design, dramatic design and top design. The Zapin Kampong Bolak dance is first made to take part in a regional dance parade contest, then also staged for entertainment and greetings in Tembilahan District, Indragiri Hilir Regency, Riau Province.  Keywords: choreography, Zapin Dance, Kampong Bolak